Distributed Generation: A Critical Review of Technologies, Grid Integration Issues, Growth Drivers and Potential Benefits - Pavan Khetrapal (International Journal of Renewable Energy Development, 2020)
Owing to liberalization of electricity market, technology evolution, energy security, environmental issues and growing concerns of energy cost, the penetration of distributed energy units in distribution network is increasingly observed worldwide. Penetratingrembedded generation, or distributedrgeneration (DG), in powerrdistribution grid requires asnumber of issues to be considered, such as definition of DG, rating of DG, the best DG technology etc. This paper presents an extensive critical review of various dimensions of distributed generation (DG) including definitions, generation technologies and their status, impact on distribution network performance etc. The study also presents comparative study between the various technologies in terms of most important technological characteristics of each DG technology. The policy makers, utility regulators and DG planning engineers can use this critical review, withoutigoing through complicatedicomputations, as guidelines to makeipolicies, standards andidecisions in DG penetration andirelated issues.